Live high-train low altitude training: responders and non- responders - Hamlin, M. J.; Manimmanakorn, A.; Creasy, R. H.; Manimmanakorn, N. (Journal of Athletic Enhancement, 2015)
Objective: Investigate differences between athletes that responded (improved performance) compared to those that did not, after a 20- day "live high-train low" (LHTL) altitude training camp.